A High Lymph Node Yield is Associated with Prolonged Survival in Elderly Patients Undergoing Curative Gastrectomy for Cancer: A Dutch Population-Based Cohort Study - Brenkman, Hylke J. F. (Ann Surg Oncol, 2017)
PURPOSE: The aim of this study was to evaluate the influence of lymph node yield (LNY) on postoperative mortality and overall survival in elderly patients with gastric cancer. METHODS: This population-based study included data from The Netherlands Cancer Registry of patients who underwent curative gastrectomy for adenocarcinoma between 2006 and 2014. Patients were divided into two groups based on age (<75 years, young; ≥75 years, elderly). LNY was analyzed as both a categorical variable (low, <15 nodes; intermediate, 15–25 nodes; high, >25 nodes), and a discrete variable. Multivariable analysis was used to evaluate the influence of LNY on 30- and 90-day mortality, as well as overall survival. RESULTS: A total of 3764 patients were included in the study; 2387 (63%) were classified as ‘young’, and 1377 (37%) were classified as ‘elderly’. The median LNY was 14 in the young group, compared with 11 in the elderly group (p < 0.001). In the elderly group, 851 (62%) patients had a low LNY, 333 (24%) had an intermediate LNY, and 174 (13%) had a high LNY. Multivariable analysis demonstrated that in the elderly patients, a higher LNY was associated with a prolonged overall survival (low: reference; intermediate: hazard ratio [HR] 0.74, 95% confidence interval [CI] 0.62–0.88, p < 0.001; high: HR 0.59, 95% CI 0.45–0.78, p < 0.001), but not with 30-day (p = 0.940) and 90-day mortality (p = 0.573). For young patients, these results were comparable. CONCLUSION: In both young and elderly patients, a high LNY is associated with prolonged survival but not with an increase in postoperative mortality. Therefore, an extensive lymphadenectomy is the preferred strategy for all patients during gastrectomy in order to provide an optimal oncological result.